Contact, threat, and prejudice: A test of intergroup threat theory across three samples and multiple measures of prejudice. (6th July 2021) - Aberson, Christopher L.; Ferguson, Hannah; Allen, Jack
Abstract: Across three studies we applied predictions from Intergroup Contact Theory and Intergroup Threat Theory (ITT) to an examination of the role of contact and threats in predicting prejudice toward three outgroups. Reactions to African Americans ( n  = 227), Hispanic Americans ( n  = 155), and gay men ( n  = 217), largely supported predictions. Positive contact experiences consistently related to more favorable evaluations and reduced perceptions of threats. Each study largely supported ITT's proposition that threats indirectly influence the contact‐prejudice relationship, with the most consistent findings found for negative contact. We found little support for relationships between contact, threats, and implicit preferences or for positive–negative asymmetry effects.